2014
DOI: 10.1016/j.atherosclerosis.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Very low density lipoprotein cholesterol associates with coronary artery calcification in type 2 diabetes beyond circulating levels of triglycerides

Abstract: Objective While recent genomic studies have focused attention on triglyceride (TG) rich lipoproteins in cardiovascular disease (CVD), little is known of very low-density lipoprotein cholesterol (VLDL-C) relationship with atherosclerosis and CVD. We examined, in a high-risk type-2 diabetic population, the association of plasma VLDL-C with coronary artery calcification (CAC). Methods The Penn Diabetes Heart Study (PDHS) is a cross-sectional study of CVD risk factors in type-2 diabetics (n=2118, mean age 59.1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 50 publications
(59 reference statements)
0
38
1
1
Order By: Relevance
“…Resultados similares foram relatados por Khalid & Siddiqui (2012), os quais ao empregarem em ratos Wistar (submetidos a uma dieta hiperlipídica) o extrato aquoso de uma planta (Punarnava) também rica em flavonóides, polifenóis e antioxidantes, assim como o EAA, obtiverem uma redução nos níveis de gordura corporal (Prenner et al 2014).…”
Section: Resultsunclassified
“…Resultados similares foram relatados por Khalid & Siddiqui (2012), os quais ao empregarem em ratos Wistar (submetidos a uma dieta hiperlipídica) o extrato aquoso de uma planta (Punarnava) também rica em flavonóides, polifenóis e antioxidantes, assim como o EAA, obtiverem uma redução nos níveis de gordura corporal (Prenner et al 2014).…”
Section: Resultsunclassified
“…So then why would levels of VLDL cholesterol (VLDL-C) solve this quandary? Perhaps it's all cholesterol not triglycerides, and this is examined in the Penn Diabetes Heart Study (PDHS) cohort and published by Prenner et al in a previous issue of Atherosclerosis [22].…”
mentioning
confidence: 99%
“…So then why would levels of VLDL cholesterol (VLDL-C) solve this quandary? Perhaps it's all cholesterol not triglycerides, and this is examined in the Penn Diabetes Heart Study (PDHS) cohort and published by Prenner et al in a previous issue of Atherosclerosis [22].Plasma apo B-100 represents pro-atherogenic particles, and noteworthy in the Prenner et al paper is the substantial weakening of the relationship between VLDL-C and coronary artery calcification (CAC) noted in the multi-adjusted Model 3 (full sample, p ¼ 0.005) when apo B was included in Model 4 (p ¼ 0.03). Because IDL and VLDL remnants would be expected to contribute a relatively small amount of apo B-100 [8], it must be assumed that this reduction in the strength of association of VLDL-C and CAC must be from LDL; unfortunately LDL-C was not co-varied in a similar manner.…”
mentioning
confidence: 99%
“…VLDLs are the major component and atherogenic particles of TGRL in the circulation. A PDHS study that examined VLDL-C as an alternative marker of TGRL demonstrated that VLDL-C levels are positively associated with increased coronary artery calcification in patients with type 2 diabetes even after adjusting for traditional risk factors [18]. Laakso et al also reported that higher VLDL-C levels are associated with an increased risk of CVD in diabetic patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Very low-density lipoprotein (VLDL) is the most atherogenic TGRL particles, and the measurement of VLDL-C is relatively straightforward and captures distinct aspects of the TGRL and serum TG [17]. A large cross-sectional study (Penn Diabetes Heart Study (PDHS)) found that higher VLDL-C levels were associated with increasing coronary artery calcification (CAC) after adjusting for numerous traditional CV risk factors in patients with type 2 diabetes [18]. …”
Section: Introductionmentioning
confidence: 99%